2020
DOI: 10.3390/genes11030273
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and In Vitro Analysis of MYO6 Variants Causing Late-onset Progressive Hearing Loss

Abstract: MYO6 is known as a genetic cause of autosomal dominant and autosomal recessive inherited hearing loss. In this study, to clarify the frequency and clinical characteristics of hearing loss caused by MYO6 gene mutations, a large-scale genetic analysis of Japanese patients with hearing loss was performed. By means of massively parallel DNA sequencing (MPS) using next-generation sequencing for 8074 Japanese families, we found 27 MYO6 variants in 33 families, 22 of which are novel. In total, 2.40% of autosomal domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Etiological studies have shown that genetic causes are the most common etiology of deafness, and approximately two-thirds of congenital/early-onset sensorineural hearing loss in developed countries is estimated to be due to genetic causes (Morton and Nance 2006). Recent studies have indicated that a significant portion of late-onset hearing loss is also due to genetic causes (Kitano et al 2017;Kobayashi et al 2018;Shinagawa et al 2020a;Yasukawa et al 2019;Oka et al 2020;Miyajima et al 2020). A series of etiological studies has demonstrated genetic disorders to be a common cause of all types of sensorineural hearing loss, but there has been no detailed genetic epidemiological data covering a wide range of ages.…”
Section: Genetic Epidemiology Based On Genetic Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Etiological studies have shown that genetic causes are the most common etiology of deafness, and approximately two-thirds of congenital/early-onset sensorineural hearing loss in developed countries is estimated to be due to genetic causes (Morton and Nance 2006). Recent studies have indicated that a significant portion of late-onset hearing loss is also due to genetic causes (Kitano et al 2017;Kobayashi et al 2018;Shinagawa et al 2020a;Yasukawa et al 2019;Oka et al 2020;Miyajima et al 2020). A series of etiological studies has demonstrated genetic disorders to be a common cause of all types of sensorineural hearing loss, but there has been no detailed genetic epidemiological data covering a wide range of ages.…”
Section: Genetic Epidemiology Based On Genetic Testingmentioning
confidence: 99%
“…Meanwhile, both the number of DNA samples and detailed clinical data are increasing, and genetic and clinical data from over 10,000 patients has been collected from 102 collaborative centers. Based on this large-cohort data, we have published a series of studies demonstrating the mutational spectrum and clinical features caused by the representative deafness genes, including GJB2 (Tsukada et al 2010), CDH23 (Miyagawa et al 2012), KCNQ4 (Naito et al 2013), OTOF (Iwasa et al 2013(Iwasa et al , 2019, mitochondrial 1555A > G and 3243A > G (Yano et al 2014), SLC26A4 (Miyagawa et al 2014), LRTOMT (Ichinose et al 2015), GRXCR1 (Mori et al 2015a), PTPRQ (Sakuma et al 2015), COCH (Tsukada et al 2015a), TMPRSS3 (Miyagawa et al 2015d), STRC (Moteki et al 2016;Yokota et al 2019), LOXHD1 (Mori et al 2015b;Maekawa et al 2019), ACTG1 (Miyagawa et al 2015b;Miyajima et al 2020), MYO15A (Miyagawa et al 2015a), POU4F3 (Kitano et al 2017), WFS1 (Kobayashi et al 2018), CLDN14 (Kitano et al 2019), EYA4 (Shinagawa et al 2020a, b), TECTA (Yasukawa et al 2019), OTOA (Sugiyama et al 2019), and MYO6 (Miyagawa et al 2015c;Oka et al, 2020). These studies were performed between 2010 and 2020.…”
Section: Genetic Epidemiology Based On Genetic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Various genes have been reported to be causative in ADNSHL families [6,8]; however, at present, there is no particular major responsible deafness gene for ADNSHL. Our screening using the same cohort clarified the frequencies for the other causative genes in ADNSHL patients; KCNQ4: 6.6% [37], POU4F3: 4% [38], TECTA: 2.9% [39], WFS1: 2.5% [40], MYO6: 2.4% [41], ACTG1: 1.1% [42], and EYA4: 0.9% [43]. Although MYH14-associated HL is rare, the present results indicated that this gene should be included in HL screening, especially that for ADNSHL.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the structural change caused by the mutation in the alpha-helix of this highly motile region could potentially affect the contiguous actin binding region. In this regard, mutations in the MYO6 motor domain alter anchoring of the membrane of stereocilia to actin filaments, leading to disruption of hair bundle organization 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%